(untitled) (Research, Society and Development, 2022)
The great technological advance observed around the world in recent decades has generated significant changes in people’s daily lives, including in the school environment. Education is currently undergoing a major change due to the insertion of information technologies in the lives of students, with a great digital influence on children’s development and learning. As a result, the way of teaching and the dynamics of the classroom have changed, requiring education professionals to renew their concepts and include modern tools in their teaching system, thus addressing this new reality. Using information and communication technologies should therefore be a fundamental strategy for bringing the reality of the classroom closer to that of the modern world. However, despite the benefits of modernization, some points about the use of technologies in pedagogical practice still need to be better developed, so that individuals are not harmed by their negative impacts.